STRATEGI PENGEMBANGAN PARIWISATA (STUDI PADA WISATA AI BELING DUSUN KUANG AMO DESA SEMPE KECAMATAN MOYO HULU) - S Syafruddin; Razi Apriansyah Mustaram; Rizaldy Septamahendra; A Asmini (Fakultas Ekonomi dan Manajemen, 2021)
This study aims to know the role of tourism awareness group (Pokdarwis) of Sempe Village in developing Ai Beling tourism potential, describe the supporting and inhibiting factors for Pokdarwis in realizing Ai Beling as a tourist destination and describe the impact of Pokdarwis in developing Ai Beling's potential as a tourist destination. This study used a qualitative approach with type of case study. Data collection was done through interview. The study subjects were the headman, the Pokdarwis chair, Pokdarwis members, community leaders, and the community. To test validity of data, the researcher used source triangulation technique. The data analysis used was qualitative analysis which consisted of data reduction steps, data display, and conclusion drawing. The results of study showed that Pokdarwis of Sempe Village played a role in introducing, preserving, and utilizing tourism potential, managing tourism, increasing the knowledge and skills of members and the community and establishing cooperation with other organizations. The supporting factors for Pokdarwis Desa Sempe, namely: government support, abundant natural resources, and preserved local wisdom. Meanwhile, the inhibiting factors were the lack of community participation and the lack of awareness and actualization of society towards charm. The impact that felt by communities of Sempe village toward the existence of Pokdarwis that with good management, the number of tourist visits were increased so that it can served jobs opportunities for communities so that could increase communities’ welfare.